2020
DOI: 10.1002/mds.28300
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Levels of Prodynorphin‐Derived Peptides are Decreased in Huntington's Disease

Abstract: RESULTS Huntingtonʼs disease (HD) is a devastating neurodegenerative disorder characterized by a selective loss of striatal medium spiny projection neurons (MSNs). Prodynorphin (PDYN) is enriched in a subpopulation of striatal MSNs. Postmortem brains of HD patients and rodent models have been demonstrated to have reduced levels of PDYN transcripts and the neuropeptide dynorphin. RESULTS Given the unmet need for novel pharmacodynamic HD biomarkers in the context of experimental huntingtin (htt)‐lowering therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
(33 reference statements)
3
18
0
Order By: Relevance
“…The biomarker SIM2 is also supposed to serve as a noble target for Down’s Syndrome-related AD 81 . Although the PDYN gene is extensively studied in Huntington’s Disease 82 , its role in AD is yet to be explored. The interacting biomarkers with AD genes in the MTG region are CDK5, GHSR, PLCB1, ITPKB, HOMER3 ( Fig 5B ).…”
Section: Discussionmentioning
confidence: 99%
“…The biomarker SIM2 is also supposed to serve as a noble target for Down’s Syndrome-related AD 81 . Although the PDYN gene is extensively studied in Huntington’s Disease 82 , its role in AD is yet to be explored. The interacting biomarkers with AD genes in the MTG region are CDK5, GHSR, PLCB1, ITPKB, HOMER3 ( Fig 5B ).…”
Section: Discussionmentioning
confidence: 99%
“…Al Shweiki et al 18 measured prodynorphin‐derived peptides and NfL in the CSF of patients with HD, matched controls, and patients with other neurodegenerative disorders using liquid chromatography–mass spectrometry for prodynorphin and established immunoassay for NfL. The levels of prodynorphin‐derived peptides in the CSF of patients with HD were smarkedly decreased in comparison with the age‐matched non‐neurodegenerative controls and also significantly decreased in comparison with patients with amyotrophic lateral sclerosis and Alzheimer's disease/mild cognitive impairment.…”
Section: Figmentioning
confidence: 99%
“…Endogenous opioids are a group of peptides that act on opioids receptors and that derive from proteolytic cleavage of three main precursors: proenkephalin (PENK), prodynorphin (PDYN) and pro-opiomelanocortin [7]. Altered levels of CSF PDYN and/or PENK-derived peptides have been reported in Alzheimer's disease (AD), frontotemporal dementia (FTD), dementia with Lewy bodies (DLB) and Huntington's disease (HD) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence from these studies suggested that decreased CSF PDYN and PENK levels may reflect an impairment and/or neurodegeneration of the striatal medium spiny projection neurons (MSNs), which produce both peptides under dopaminergic signaling [9,10]. Moreover, dysfunctions in the PDYN pathway appear to be involved in developing behavioral and sleep disorders in neurodegenerative disease [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation